2012
DOI: 10.1186/2193-1801-1-35
|View full text |Cite
|
Sign up to set email alerts
|

Presence of chelonid fibropapilloma-associated herpesvirus in tumored and non-tumored green turtles, as detected by polymerase chain reaction, in endemic and non-endemic aggregations, Puerto Rico

Abstract: Fibropapillomatosis (FP), a transmissible neoplastic disease of marine turtles characterized by a likely herpesviral primary etiology, has emerged as an important disease in green sea turtles (Chelonia mydas) over the past three decades. The objectives of this study were to determine the suitability of three different chelonid fibropapilloma-associated herpesvirus (CFPHV) gene targets in polymerase chain reaction (PCR) assays of affected tissues; to explore the presence of CFPHV in non-affected skin from turtl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 29 publications
(73 reference statements)
5
50
1
1
Order By: Relevance
“…Our finding that 83.3% of non-tumored skin samples from FP+ turtles (turtles with FP) tested positive for ChHV5 DNA is similar to a previous study, in which 88% of FP+ green turtles had non-tumored skin samples that tested positive for ChHV5 DN A by qPCR (Alfaro-N úñez et al 2014). Our findings that skin samples from 7/28 (25%) of tumor-free turtles were positive for ChHV5 DN A via qPCR is also similar to the results of another study, in which 32.4% of skin samples from tumor-free turtles were positive for ChHV5 DNA via nested PCR (Page-Karjian et al 2012).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our finding that 83.3% of non-tumored skin samples from FP+ turtles (turtles with FP) tested positive for ChHV5 DNA is similar to a previous study, in which 88% of FP+ green turtles had non-tumored skin samples that tested positive for ChHV5 DN A by qPCR (Alfaro-N úñez et al 2014). Our findings that skin samples from 7/28 (25%) of tumor-free turtles were positive for ChHV5 DN A via qPCR is also similar to the results of another study, in which 32.4% of skin samples from tumor-free turtles were positive for ChHV5 DNA via nested PCR (Page-Karjian et al 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Although several previous studies have identified ChHV5 DN A in FP tumors and non-tumored skin (Lackovich et al 1999, Lu et al 2000, Quackenbush et al 2001, Page-Karjian et al 2012, AlfaroNúñez et al 2014), here we provide novel evidence for the presence of ChHV5 DNA in blood, urine, cloacal swabs, and plasma from turtles with and without FP tumors. This study provides critical information for a deeper understanding of the complex ChHV5 pathogenesis in symptomatic and asymptomatic turtles.…”
Section: Discussioncontrasting
confidence: 38%
See 3 more Smart Citations